Application of a scattering foil to increase beam transmission for cyclotron based proton therapy facilities - Maradia, Vivek; Meer, David; Weber, Damien Charles; Lomax, Antony John; Schippers, Jacobus Maarten; Psoroulas, Serena (Frontiers in Physics, 2022)
In proton therapy, high dose rates can reduce treatment delivery times, allowing for efficient mitigation of tumor motion, as well as increased treatment efficiency and patient throughput. In cyclotron-based facilities, however, high dose rates are difficult to achieve at low-energies. In current facilities, the emittance after the degrader is matched in both transversal planes using circular collimators; this however does not provide an optimal matching to the acceptance of the following beamline. However, transmission can be substantially improved by transporting maximum acceptable emittances in the X and Y planes, but at the cost of an elliptical beam shape at the gantry entrance, leading to gantry angle-dependent beam shapes at the isocenter. Here we demonstrate that equal emittances in both planes can be recovered at the gantry entrance using a thin scattering foil, thus ensuring gantry angle-independent beam shape at the isocenter. Using modified beam optics and thin scattering foil placed in the beamline, we demonstrate experimentally that low-energy beam transmission can be increased by a factor of 3 compared to the currently used beam optics, whilst preserving gantry angle-independent beam shapes. We expect that this universal approach could also bring a similar transmission improvement in other cyclotron-based proton therapy facilities.